A strategic approach for a SME venturing into a transitional economy : Vietnam - Chow, Man Wai (2014)
Since the early nineties, the Singapore government realised the need to create a “second wing" to supplement the domestic economy. They forsee that the small Singapore economy is incapable to substain the current high growth rates. At the same time, the government also wants to reduce reliance on multinational corporations.